2018
DOI: 10.1074/mcp.ra117.000431
|View full text |Cite
|
Sign up to set email alerts
|

Proteotranscriptomic Analysis and Discovery of the Profile and Diversity of Toxin-like Proteins in Centipede

Abstract: SummaryCentipedes are one of the oldest venomous animals and use their venoms as weapons to attack prey or protect themselves. Their venoms contain various components with different biomedical and pharmacological properties. However, little attention has been paid to the profiles and diversity of their toxin-like proteins/peptides. In this study, we used a proteotranscriptomic approach to uncover the diversity of centipede toxin-like proteins in Scolopendra subspinipes mutilans. Nine hundred twentythree and 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The vast majority of studies of centipede venom are restricted to the Scolopendra genus [8][9][10]27,[29][30][31][32][33]. In addition, some studies use the whole centipede instead of the whole venom for their proteomics analyses, making a more specified comparison inviable [34,35]. Five comparative studies have demonstrated that centipede venoms are complex cocktails, encompassing more than 60 phylogenetically distinct protein families [10,32,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies of centipede venom are restricted to the Scolopendra genus [8][9][10]27,[29][30][31][32][33]. In addition, some studies use the whole centipede instead of the whole venom for their proteomics analyses, making a more specified comparison inviable [34,35]. Five comparative studies have demonstrated that centipede venoms are complex cocktails, encompassing more than 60 phylogenetically distinct protein families [10,32,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Centipede venom contains an abundance of peptide toxins. With advances in transcriptomics and proteomics, the composition of centipede venom was confirmed through continuing effort [8,10,39,40]. Liu et al profiled the venom proteome and gland transcriptome from Scolopendra subspinipes dehaani and characterized 40 peptides [39].…”
Section: Centipede Toxins As An Abundant Source Of Drug Leadsmentioning
confidence: 99%
“…Rong et al also focused on the diversity of centipede venom and obtained 79 unique peptide toxins from the venom of Scolopendra subspinipes mutilans [10]. Recently, Zhao et al identified 1204 unique proteins in the torso tissue and 165 unique proteins in the venom gland peptides of Scolopendra subspinipes mutilans using proteotranscriptomics [8].…”
Section: Centipede Toxins As An Abundant Source Of Drug Leadsmentioning
confidence: 99%
See 2 more Smart Citations